STRUKTUR DAN KEANEKARAGAMAN JENIS VEGETASI MANGROVE DI PESISIR PANTAI KELAPA TINGGI DESA MATA AIR - Maria Rika Tufan; Mario J Santrum; Nikmah Nikmah (SINERGI : Jurnal Riset Ilmiah, 2026)
This research is about the structure and diversity of mangrove vegetation species on the Coconut Beach Coast, Mata Air Village, Central Kupang District, Kupang Regency, carried out with the aim of understanding the structure and diversity of mangrove vegetation species on the Coconut Beach Coast, Mata Air Village, Central Kupang District, Kupang Regency. This research was conducted on the Coconut Beach Coast, Mata Air Village, Central Kupang District, Kupang Regency in August 2025. The method used in this study is the line transect method by using 7 observation transects, each transect consisting of 3 plots. The parameters of this study are to understand the structure of mangrove vegetation and the diversity of mangrove species on the Coconut Beach Coast. Based on the results of the research conducted on the structure and diversity of mangrove vegetation on the Coconut Beach Coast, 7 types of mangroves were found, namely Avicennia marina, Sonneratia alba, Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Ceriops tagal, and Excoecaria agallocha. The species with the highest INP value is Avicennia Marina at 80.90%, and the diversity value of mangrove vegetation species at Kelapa Tinggi Beach is considered moderate with an H’ value of 1.81.